Analisis Kandungan Sibutramin HCl pada Jamu Pelangsing dengan Metode Spektrofotometri UV-Vis - Kholif, Kholif Sholehah Indra K; Kurniawati, Endah; Komalasari, Desy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background: Plant, mineral, animal, extract (galenic) preparations, or a combination of various ingredients form the basis of jamu, a type of traditional herbal medicine. Herbal medicine has been applied in treatment based on experience, where its benefits and safety have been proven empirically. One type of herbal medicine popular with the public, especially women, is slimming herbal medicine. As the demand for slimming herbal medicine increases, some parties capitalize on this trend by adding medicinal chemicals (BKOs). Sibutramine HCl is a commonly added BKO in slimming herbal medicine. Objective: To qualitatively and quantitatively analyze the sibutramine HCl content in herbal slimming powders circulating in the Yogyakarta city market. Method: This type of research is non-experimental descriptive with a purposive sampling technique. The samples used in this research were 10 herbal slimming powders with various brands circulating in the Yogyakarta City market. Sample analysis was carried out qualitatively using the Thin Layer Chromatography method and wavelength scanning. Meanwhile, quantitative analysis was carried out using UV-Vis Spectrophotometry. Results: The results of qualitative and quantitative sample analysis showed that from 10 samples, 2 samples were positive for containing sibutramine HCl in samples A and B. The sibutramine HCl content in sample A was 2,4377 ± 0,0066%w/w and B was 1,0164 ± 0,0114%w/w. Conclusion: There is BKO sibutramine HCl content in the powdered slimming herbal medicine samples with respective levels of 2,4377 ± 0,0066%w/w and 1,0164 ± 0,0114%w/w.